Here is the problem.....√(15x + 10) = 2x+3
to remove the square root, we do the opposite which is to square everything.
(√(15x + 10))² = (2x + 3)² (the square negates the square root)
15x + 10 = (2x +3)(2x + 3) (use the distributive property to continue)
15x + 10 = 4x² + 6x + 6x + 9 (combine like terms)
15x + 10 = 4x² + 12x + 9 (subtract 15x and 10 from each side)
-15x - 10 -15x - 10
0 = 4x² - 3x - 1 (factor completely)
(x - 1) (4x + 1) (set each to equal 0)
x - 1 = 0 4x + 1 = 0
x = 1 4x = -1
x = -1/4
place both into the equation to check for reasonableness...we see the negative number is not reasonable, but the x value of 1 is a solution.
answer is 1
<h3>
Answer: Solution is x = -2</h3>
You have two equations with y1 = f(x) and y2 = g(x).
We're looking for the values of x such that f(x) = g(x). This is the same as trying to solve y1 = y2.
The first row of the table shows y1 and y2 having the same value 5. So we just record the x value that goes with these y values.
Since area is length times width, it would be the factors of the equation for the area.
X2+11x+28 factors into...
Length is x+7 so...
Width is x+4
Answer:
Step-by-step explanation: multiply 4 by 12 then 4 by 3 then 4 by 9.